Phylogenetic analysis of pigeonpea (Cajanus cajan) genotypes using Panzee retrotransposon based SSAP markers - PATIL, PRAKASH; DATTA, S; SINGH, I P; DAS, ALOK; SOREN, K R; KAASHYAP, M; CHOUDHARY, A K; CHATURVEDI, S K; NADARAJAN, N (The Indian Journal of Agricultural Sciences, 2013)
In the present study, twenty one pigeonpea [Cajanus cajan (L.) Millspaugh] genotypes representing three different gene pools were analysed for phylogenetic relationships using sequence specific amplification polymorphism markers. Four primers were screened involving selective AFLP primers in combination with primer specific to 5'LTR region of Panzee retrotransposon. A total of 183 bands were scored, out of which 166 (90.71%) bands were polymorphic with an average of 41.5 polymorphic bands per primer combination. Polymorphism information content (PIC) values ranged from 0.15 [Panzee-LTR/ EcoRI (+AAC)] to 0.26 [Panzee-LTR/ EcoRI (+AAG)] for four primer combinations. Resolving power (RP) values ranged from 10.14 [Panzee-LTR/ EcoRI (+AAC)] to 24.92 [Panzee-LTR/ MseI (+CAC)], whereas marker index (MI) values ranged from 5.25 [Panzee-LTR/ EcoRI (+AAC)] to 14.25 [Panzee-LTR/ MseI (+CAC)] exhibiting positive correlation (r2=0.99 P